Anticancer effects of resveratrol in canine hemangiosarcoma cell lines. (13th December 2017) - Carlson, A.; Alderete, K. S.; Grant, M. K. O.; Seelig, D. M.; Sharkey, L. C.; Zordoky, B. N. M.
Abstract : Hemangiosarcoma (HSA) is a highly malignant tumour with aggressive biological behaviour. HSAs are more common in dogs than other domestic animals. The median survival time of dogs with HSA remains short, even with chemotherapy and surgery. Therefore, there is a critical need to improve the adjuvant chemotherapeutic regimens to improve clinical outcomes in dogs with HSA. Resveratrol has been shown to possess strong anti‐proliferative and/or pro‐apoptotic properties in human cancer cell lines. Nevertheless, the potential anticancer effects of resveratrol have not been reported in canine HSAs. The objective of this study is to determine the growth inhibitory effects of resveratrol in HSA cells when used alone or in combination with doxorubicin, a commonly used chemotherapeutic agent. Frog and DD‐1 canine HSA cell lines were treated with varying concentrations of resveratrol with and without doxorubicin. Cell viability was measured by the MTT assay. The expression of apoptotic proteins, activation of p38 mitogen‐activated protein kinase (MAPK), AMP‐activated protein kinase (AMPK) and extracellular signal‐regulated kinase 1/2 (ERK1/2) were assessed by western blotting. Similar to human cancer cell lines, resveratrol markedly inhibited the growth and induced apoptosis in both HSA cell lines. Mechanistically, resveratrol activated p38 MAPK, but did not affect the AMPK or the ERK1/2 pathways. Additional experiments showed that resveratrol augmented the growth‐inhibitory and apoptotic effects of doxorubicin in both HSA cell lines. These findings suggest that resveratrol has pro‐apoptotic effects in canine HSA cells; therefore, its use as a potential adjunct therapy in canine HSA patients warrants further investigation.